Penerapan Kombinasi Terapi Relaksasi Benson dan Senam Kaki Diabetes terhadap Perubahan Gula Darah Sewaktu pada Ny. SR dengan Diabetes Melitus Tipe 2 - Regifta, Sherly Amor; Rahayu, Henik Tri (Pustaka Galeri Mandiri, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by elevated blood glucose levels and is associated with various complications, including peripheral neuropathy and circulatory disorders. Non-pharmacological interventions are needed to support glycemic control and improve patients’ quality of life. Benson Relaxation Therapy and diabetic foot exercises are complementary approaches that may help reduce blood glucose levels and enhance peripheral circulation. Objective To determine the effectiveness of the combination of Benson Relaxation Therapy and diabetic foot exercises in reducing blood glucose levels in a patient with Type 2 Diabetes Mellitus. Methods This study was a case study employing a nursing care approach with a pre-test and post-test design without a control group. The research subject was a 65-year-old female patient with Type 2 Diabetes Mellitus. The intervention consisted of a combination of the Benson relaxation technique and diabetic foot exercises administered for three consecutive days. Evaluation was conducted by measuring blood glucose levels and blood pressure before and after the intervention. The intervention resulted in a reduction in blood glucose levels from 258 mg/dL to 149 mg/dL, representing a total decrease of 109 mg/dL. Blood pressure improved from 150/70 mmHg to 120/70 mmHg. The patient also reported reduced numbness and increased warmth in the feet, indicating improved peripheral circulation. The combination of Benson Relaxation Therapy and diabetic foot exercises appears effective in reducing blood glucose levels, stabilizing blood pressure, and improving peripheral circulation, making it a beneficial complementary therapy for holistic management of Type 2 Diabetes Mellitus.